PARTISIPASI PEREMPUAN DALAM AKSI PENOLAKAN PENAMBANGAN GUNUNG TUMPANGPITU (Suatu Analisis Ekofeminisme) - Saputra, Rico Amdan; Handayani, Baiq Lily (Jurnal ENTITAS SOSIOLOGI, 2018)
The primary purpose of this research is to see and analyze how women participate in the rejection of Tumpangpitu mount gold mining in Sumberagung village, Pesanggaran ? Banyuwangi by using the descriptive qualitative method.  Data collected by interview, direct and visual observation, and literature review. The theory used for the analysis is Ecofeminism Vandana Shiva, approached with (PAR). The researcher also involved in the rejection action. The result of the research shows that women, directly engaged in this environment struggle, without any command but came from their desire. Most of them have a low education level, but they realized that of the environment damaged, they would be alienated from their income resources and family life. Considering a child is an invitation for parent and their future. They fear the damaged ecosystem will affect the difficulty of finding resources of growth and income due to gold mining.   Keywords: Womens Participation, Ecofeminism, Tumpangpitu, Environment, Mining Gold